Pengaruh Pemikiran Etis, Relativiseme dan Idealisme terhadap Sensitivitas Etis mahasiswa Akuntansi: (Studi Empiris di Jurusan Akuntansi Fakultas Ekonomi Bisnis Universitas Pattimura) - Angel Merlyn Pattimahu (P3M Politeknik Negeri Ambon, 2022)
Each accounting student is expected to have knowledge, understanding, and applying ethics adequately in the learning process so that later can be applied in the implementation of his professional work. This study aims to identify and empirically test the influence of ethical thinking, idealism, and relativism, on sensivity of accounting students. Data from this study were collected from accounting students S1, faculty of Economic, Pattimura University with criteria accounting students who passed the course of auditing 1 and auditing 2 with an A or B. Data obtained by distributing directly to the students asa much as 150 questionnaires and 127 questionnaires were used as samples for analysis. Data analysis using XLSTAT-PLS applications. The results showed that ethical thinking positive effect on ethical sensivity. Next idealism positive effect on ethical sensivity. Which follows relativism has no effect on ethical sensivity. Keywords : ethical thinking, idealism, relativism, ethical sensivity.